2020
DOI: 10.1007/s11540-020-09481-x
|View full text |Cite
|
Sign up to set email alerts
|

Hilling of Transplanted Seedlings from Novel Hybrid True Potato Seeds Does Not Enhance Tuber Yield but Can Affect Tuber Size Distribution

Abstract: A novel cropping system for potato was tested for two consecutive years under normal Dutch agronomic conditions. Seedlings from two experimental genotypes of hybrid true potato seeds were produced in a greenhouse nursery and transplanted into the field 5 weeks after sowing to assess tuber yield levels and to study effects of hilling on tuber yield and number, tuber size distribution and tuber greening. Field experiments had a split-plot design with hilling treatments as the main plots and genotypes as the sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 39 publications
0
73
0
Order By: Relevance
“…It is suggested that more cultivar-specific trials are conducted when improved hybrid potato cultivars become available to growers. These studies will contribute with the current study, and those carried out by Kacheyo et al (2021), Stockem et al (2020) and van Dijk et al (2021), useful information on the novel cultivation systems for hybrid potato, including crop management recommendations. More information will also be required on the optimal field conditions at the moment of transplanting and the subsequent seedling establishing period to enhance quick plant development.…”
Section: Further Studiesmentioning
confidence: 83%
See 3 more Smart Citations
“…It is suggested that more cultivar-specific trials are conducted when improved hybrid potato cultivars become available to growers. These studies will contribute with the current study, and those carried out by Kacheyo et al (2021), Stockem et al (2020) and van Dijk et al (2021), useful information on the novel cultivation systems for hybrid potato, including crop management recommendations. More information will also be required on the optimal field conditions at the moment of transplanting and the subsequent seedling establishing period to enhance quick plant development.…”
Section: Further Studiesmentioning
confidence: 83%
“…Both experimental hybrids originated from the breeding programme described by Lindhout et al (2018) and were derived from similar research lines as the hybrids studied by Stockem et al (2020). Hybrid true seeds were sown by hand in 104-plug nursery trays on 13 April in 2017 and on 3 April in 2018 and cultivated as described by van Dijk et al (2021). Five weeks after sowing, 1 day prior to transplanting, a selection of transplantable seedlings (measuring 7-12 cm above-ground, containing 5-8 true leaves, BBCH stage 105-108; Kacheyo et al 2021) was made consistent with the protocol of van , after which seedlings were irrigated and loaded for transport to the field locations.…”
Section: Hybrid Potato Genotypes and Greenhouse Nurserymentioning
confidence: 99%
See 2 more Smart Citations
“…One of the factors that leads to variation in potato plants is the quality of the seed tubers (Struik and Wiersema 2012). When testing hybrids, an alternative to using seed tubers as starting material is to use seedlings from true seed to prevent variation due to seed tuber quality, also from seedlings from true seeds relatively high yields up to 32 Mg/ha can be reached (Van Dijk et al 2021).…”
Section: Optimal Plot Size Differs For Different Traitsmentioning
confidence: 99%